PENCEGAHAN TERJADINYA RESIKO DE QUERVAIN SYNDROM PADA PENGGUNA GADGET - Nova Relida Samosir; Ayu Permata; Siti Muawanah (Jurnal Pengabdian Masyarakat Multidisiplin, 2019)
Background: The use of Information and Communication Technology (ICT) devices is very broad, almost all human activities cannot be separated from technological devices, one example of which is the use of gadgets such as mobile phones, smartphones and tablets. Not many realize that using a gadget can pose a number of risks. Risks that can arise are De Quervain Syndrome. De Quervain Syndrome is a form of inflammation of the tendon membrane which is accompanied by pain at the base of the thumb extending to the lower arm, the presence of tendon swelling and causing and involving the narrow tendon movement (known as tenosynovitis) which is in synovial sheaths, that is covering the abductor pollicis longus and extensor pollicis brevis muscles. The purpose of this community service is to find out the impact of knowledge on the prevention of the risk of de quervain syndrome in gadget users at Muhammadiyah 2 Vocational School Pekanbaru-Riau. Methodology: this community service is in the form of lectures and discussions, examinations and measurements of early detection on the scale of pain with a VAS (Verbal Analog Scale) scale. Descriptive data analysis technique. Results and discussion: of community service activities were attended by students with a total of 54 people ranging in age from 15 to 17 years. In the number of students 54, the average value of pre-test and post-test, there is an increase in knowledge by 40%. Conclusion: There is an impact of increasing knowledge in students about the benefits of preventing the risk of de quervain syndrome in gadget users at Muhammadiyah 2 Vocational School Pekanbaru-Riau. Keywords: De Quervain Syndrom, Verbal Analog Scale, Gadget